A Study of the Distributions of Two Endangered Sea Skaters Halobates matsumurai Esaki and Asclepios shiranui (Esaki) (Hemiptera: Gerridae: Halobatinae) with Special Reference to Their Strategies to Cope with Tidal Currents - Terumi Ikawa; Yuichi Nozoe; Natsuko Yamashita; Namiko Nishimura; Satoshi Ohnoki; Kyoko Yusa; Sugihiko Hoshizaki; Masayuki Komaba; Akihiro Kawakubo (Psyche: A Journal of Entomology)
There exist surprisingly few marine insects, most of which are confined to the intertidal zone. Halobates is the only genus to have some oceanic species along with some coastal species. Among the coastal sea skaters, that is, genus Halobates and its close relative, genus Asclepios, there are variations in their affinity for the shore. We have studied the distributions of two endangered Japanese sea skaters, Halobates matsumurai and Asclepios shiranui in Kujukushima, where they cooccur in coves. To compare their survival strategies at sea, we especially noted differences in their distributions along the shore during high and low tides. The results show that A. shiranui tended to remain along the shore during low tide. This species appeared to cling to the shore against the ebb current and to stay in the protected coves. By contrast, H. matsumurai tended to leave the shore during low tide. Notably, some adults were found skating outside the coves. The strategy of H. matsumurai appeared to be leaving with the ebb current even beyond the coves, thereby using more resources and enlarging its habitat. Some such coastal Halobates might have acquired the ability to live on the open ocean clearly independent of the shoreline.